2014
DOI: 10.1186/cc13174
|View full text |Cite
|
Sign up to set email alerts
|

Multiple gene-to-gene interactions in children with sepsis: a combination of five gene variants predicts outcome of life-threatening sepsis

Abstract: IntroductionThe aim of the study was to identify the dependency structure of genetic variants that can influence the outcome for paediatric patients with sepsis.MethodsWe evaluated the role of single nucleotide polymorphisms for five genes: bactericidal permeability increasing protein (BPI; rs5743507), lipopolysaccharide-binding protein (LBP; rs2232618), toll-like receptor 4 (TLR4; rs4986790), heat shock protein 70 (HSP 70; rs2227956), and interleukin 6 (IL-6; rs1800795) in 598 children aged 0 to 19 years that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 39 publications
1
35
0
3
Order By: Relevance
“…The majority of previous studies related to SNPs in sepsis were performed on adults [36]. However, data from neonate populations with sepsis are poor, and developmental differences that affect inflammation and immune responses make it difficult to extrapolate data from adult studies to newborn populations [8,48]. The current study focused on analyses of SNPs in four genes (IL-1β 65-5.38), p value = 0.004) -31 T/C, IL-6 -174 G/C, TNF-α -308 G/A, and IFN-γ +874 A/T) that may play a critical role in, or are associated with, inflammatory response and sepsis severity, in order to identify possible predictive mechanisms for sepsis risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies related to SNPs in sepsis were performed on adults [36]. However, data from neonate populations with sepsis are poor, and developmental differences that affect inflammation and immune responses make it difficult to extrapolate data from adult studies to newborn populations [8,48]. The current study focused on analyses of SNPs in four genes (IL-1β 65-5.38), p value = 0.004) -31 T/C, IL-6 -174 G/C, TNF-α -308 G/A, and IFN-γ +874 A/T) that may play a critical role in, or are associated with, inflammatory response and sepsis severity, in order to identify possible predictive mechanisms for sepsis risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Despite previous studies have indicated genetic variants combined and/or into the traditional risk model could enhance the discriminatory capacity. For example, Jabandziev et al [33] demonstrated specific combinations of five polymorphisms in the BPI (rs5743507), LBP (rs2232618), TLR4 (rs4986790), HSP70 (rs2227956), and IL-6 (rs1800795) genes appeared to predict outcome of life-threatening sepsis in children. Shimada's study [34] indicated the combined panel of TNFA − 308G/A and IL1B -31C/T plus APACHE II score might enable more accurate prediction of outcome in septic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite previous studies have indicated genetic variants combined and/or into the traditional risk model could enhance the discriminatory capacity. For example, Jabandziev et al [33] demonstrated speci c combinations of ve polymorphisms in the BPI (rs5743507), LBP (rs2232618), TLR4 (rs4986790), HSP70 (rs2227956), and IL-6 (rs1800795) genes appeared to predict outcome of life-threatening sepsis in children. Shimada's study [34] indicated the combined panel of TNFA − 308G/A and IL1B -31C/T plus APACHE II score might enable more accurate prediction of outcome in septic patients.…”
Section: Discussionmentioning
confidence: 99%